FETAL RISK ECLAMPSIA - Maradiegue Méndez, Eduardo (2015)
In the General Hospital Base Cayetano Heredia retrospective study of 28 newborns of mothers with eclampsia was carried out between June 1969 to June 1974, fetal mortality was 21.3% in hospital fetal mortality corrected 15.5%, there was also 22.6% newborns with severe hypoxia, 23.5% with moderate hypoxia and 32.1% with mild hypoxia. Multiparous patients and spontaneous labors had the highest percentage of fetal mortality, fetal mortality only had the variety of antepartum eclampsia, fetal mortality and severe hypoxia are inversely proportional to fetal weight. We had abdominal fetal mortality in childbirth.